2005
DOI: 10.1089/hyb.2005.24.14
|View full text |Cite
|
Sign up to set email alerts
|

Monoclonal Antibodies 1B3 and 5C8 as Probes for Monitoring the Integrity of the C-Terminal End of Soluble Angiotensin-Converting Enzyme

Abstract: Angiotensin-converting enzyme (ACE) is a membrane-anchored ectoprotein that is proteolytically cleaved, yielding an enzymatically active soluble ACE. Two mouse monoclonal antibodies, MAbs 1B3 and 5C8, were generated to the C-terminal part of human soluble ACE. MAb 1B3 recognized the catalytically active ACE, as revealed by ELISA and precipitation assays, whereas Western blotting and immunohistochemisty on paraffin- embedded sections using MAb 5C8 detected denatured ACE. MAb 1B3 showed extensive cross-reactivit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
63
0

Year Published

2005
2005
2021
2021

Publication Types

Select...
8

Relationship

6
2

Authors

Journals

citations
Cited by 25 publications
(63 citation statements)
references
References 48 publications
0
63
0
Order By: Relevance
“…Gln1069 (brown) is located right under the bump created by Lys1067 and Tyr1068 (purple) and shown by arrow. Dark blue indicates the first N-terminal amino acid residue (Asp616) seen in this structure; orange-indicates the C terminal end of the C-domain (and the epitope for mAb 1B3; [16], [36]. Light blue (P730) and red colored amino acid residues indicate highly immunogenic bumps on the surface of the C-domain.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Gln1069 (brown) is located right under the bump created by Lys1067 and Tyr1068 (purple) and shown by arrow. Dark blue indicates the first N-terminal amino acid residue (Asp616) seen in this structure; orange-indicates the C terminal end of the C-domain (and the epitope for mAb 1B3; [16], [36]. Light blue (P730) and red colored amino acid residues indicate highly immunogenic bumps on the surface of the C-domain.…”
Section: Resultsmentioning
confidence: 99%
“…Eight mAbs recognize epitopes on the catalytically active N-domain [15], [30], [32][34] and 8 mAbs recognize epitopes localized on the C-domain of ACE [16], [36]. We recently demonstrated that the pattern of precipitation of ACE activity (conformational fingerprinting of ACE) using this set of mAbs provides a sensitive means of identifying changes in local conformation of ACE due to inactivation, inhibition, mutations, etc.…”
Section: Resultsmentioning
confidence: 99%
“…We performed Western blotting of ACE purified from plasma of subject N1 using two mAbs to denatured human ACE: mAb 1D8, which recognizes a sequential epitope at the beginning of C domain [46], and mAb 5C8, which is directed to the C-terminal end of soluble ACE and of which binding was dramatically decreased to mutant P1199L ACE [47]. Binding of 5C8 was significantly abolished with both P1199L and W1197X mutants, whereas mAb 1D8 recognized similarly both wild-type and mutant ACE (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…We recently observed reduced binding of soluble ACE in Dutch patients with a Pro1199Leu substitution detected by a new monoclonal antibody (mAb), 1B3, which recognizes a Pro 1199 -containing epitope in the C-terminal region of soluble ACE (25 ). We therefore set out to develop a method that would use mAb 1B3 in combination with mAb 9B9 to the central part of the N-domain of ACE (26 -28 ), which would enable us to distinguish persons with the Pro1199Leu mutation from patients with increased ACE attributable to other diseases, such as sarcoidosis and Gaucher disease.…”
mentioning
confidence: 99%
“…For immunocapture studies, the following mAbs to human ACE were used: mAb 1B3, which recognizes a C-terminal part of soluble ACE (25 ), and mAbs 9B9 (26 -28 ) and 2B11, which recognize epitopes in the N-and C-domains of ACE, respectively. ACE activity in human serum or plasma was measured by a fluorometric assay (30,31 ).…”
mentioning
confidence: 99%